Ghosts, Stars, and Learning Online: Analysis of Interaction Patterns in Student Online Discussions - Samuels-Peretz, Debbie (International Review of Research in Open and Distributed Learning, 2014)
Discussions are commonly used in online teaching and have been shown to foster student learning and collaboration. This case study uses content analysis to explore the interaction patterns of student online discussions during a semester-long teacher preparation course using concepts from sociometry. Findings suggest that interaction patterns were influenced by the content of student posts. Online discussions in this case were found to be an equitable form of collaborative learning, enabling each student to have a voice. There were, however, indications that gendered ways of knowing may play a role in the content of interaction, if not in the patterns themselves.